1996
DOI: 10.1042/bj3180001
|View full text |Cite
|
Sign up to set email alerts
|

The lipocalin protein family: structure and function

Abstract: The lipocalin protein family is a large group of small extracellular proteins. The family demonstrates great diversity at the sequence level ; however, most lipocalins share three characteristic conserved sequence motifs, the kernel lipocalins, while a group of more divergent family members, the outlier lipocalins, share only one. Belying this sequence dissimilarity, lipocalin crystal structures are highly conserved and comprise a single eight-stranded continuously hydrogen-bonded antiparallel β-barrel, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
1,293
1
19

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,540 publications
(1,328 citation statements)
references
References 137 publications
(154 reference statements)
15
1,293
1
19
Order By: Relevance
“…Sequence analysis revealed that the N-terminal portion of both wheat and Arabidopsis proteins possesses the three lipocalin SCRs. The SCR 1 region is located within aa 15^31 (GLDVARYMGRWYEIASF) in TaTIL and within aa 12^28 (GLNVERYMGRWYEIASF) in AtTIL and possesses the two conserved amino acids G and W [1,9] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence analysis revealed that the N-terminal portion of both wheat and Arabidopsis proteins possesses the three lipocalin SCRs. The SCR 1 region is located within aa 15^31 (GLDVARYMGRWYEIASF) in TaTIL and within aa 12^28 (GLNVERYMGRWYEIASF) in AtTIL and possesses the two conserved amino acids G and W [1,9] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 28S ribosomal band stained with ethidium bromide is included to show RNA loads (7.5 Wg). NA7, NA12, non-acclimated plants grown for 7 and 12 days; CA1, CA6, CA36, cold-acclimated plants for 1,6 and 36 days; DA1 and DA5, coldacclimated plants (36 days) were deacclimated for 1 and 5 days; NaCl, plants treated with 300 mM NaCl for 18 h; ABA, plants treated with 0.1 mM ABA (Sigma) for 18 h; WS, water-stressed plants with a relative water content of 57% and 44%; HS, plants exposed to 40 ‡C for 1 h and 3 h (heat-shock); W, wounding stress for 3 h. Leaf, crown and roots of non-acclimated plants (NA7) and 6 days cold-acclimated (CA6). ARA, Arabidopsis plants; NA, nonacclimated plants; CA1, cold-acclimated for 1 day; HS 1 h, exposed to 45 ‡C for 1 h (heat-shock).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2010). The LD prepupae also preferentially expressed at least one member of the lipocalin family of transporters, which carry small hydrophobic molecules such as steroids and lipids, and may play a role in insect coloration, immunity, olfaction and pheromone transport (Flower 1996). We also found that LD prepupae expressed higher levels of prophenoloxidase‐activating factor, which presumably activates the prophenoloxidase required for melanin formation in the darker summer phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis of the binding area resulted in a number of efficient affibodies that bind targets like human insulin or the cytokine TNFα 39. Anticalins are derived from the ß‐barrel‐structured lipocalins, a diverse class of proteins responsible for the transport, storage, synthesis, and sequestration of small hydrophobic molecules 40. Lipocalin‐based libraries have enabled the selection of anticalins against various targets with up to picomolar affinities 34.…”
Section: Recombinant Antigen‐binding Proteins: Nanobodies and Othersmentioning
confidence: 99%